Related Factors of a Nurse Handover Implementation in the Inpatient Ward of Ulin Hospital, Banjarmasin - Ahmad Juliadi; Bahrul Ilmi; Hiryadi Hiryadi (Jurnal Ners, 2019)
Introduction: Ideally, a handover is carried out through three stages: preparation, implementation, and post-handover. However, some handovers only consist of one phase. The aim of the study was to identify and analyze the factors related to the implementation of nurse handover.Methods: This was a correlative analytic research method with a cross-sectional approach. The population in this study was all of the nurses with at least a Diploma III inpatient ward education. The sample totaled 174 nurses in the inpatient ward of Ulin Hospital Banjarmasin, recruited through proportionate stratified random sampling. The data was collected by spreading the questionnaire and the data collection took place from December 2017 to January 2018.Results: There was a correlation between education level (p= 0.036) and role model (p= 0.021) with the implementation of handover. The most dominant factor associated with the implementation of handover was role model (p= 0.031: OR= 6.089).Conclusion: The nurses who had a good role model performed th handover 6.089 times better than the nurses with an inadequate role model. Adversely, a poor role model might result in a poor handover.